2017
DOI: 10.1186/s12879-017-2931-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of Xpert MTB/RIF assay on sputum sediment samples obtained from presumptive pulmonary tuberculosis cases at Kibong’oto infectious diseases hospital in Tanzania

Abstract: BackgroundThe introduction of Xpert MTB/RIF assay (Xpert) has significantly improved diagnosis of Tuberculosis (TB) in resource limited human immunodeficiency virus (HIV) endemic settings. We aimed to modify the Xpert protocol to improve the detection of Mycobacterium tuberculosis (MTB).MethodsThis cross sectional study was conducted among presumptive pulmonary tuberculosis (PTB) patients at Kibong’oto Infectious Diseases Hospital between August and November 2015. Each patient consented to provide 2 samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Studies have shown phenotypic susceptibility tests to serve as reference standards [25], and that both Xpert assay and DST can provide information on polyresistance in pre-XDR-TB [26] despite varying sensitivities [27,28]. The current practice in diagnosing drug resistant tuberculosis is through the WHO-approved probe-based assays like Xpert® MTB/RIF (Cepheid, USA) for RIF [16] and either genotype MTBDRplus for RIF and INH or genotype MTBDRsl (Hain Lifesciences, Germany) for aminoglycosides/capreomycin and fluoroquinolones that must be confirmed with culture-based DST [29]. Unlike WGS, these assays not only have limited DST range to identify hot-spot resistant determining regions but they also cannot inform transmission dynamics [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown phenotypic susceptibility tests to serve as reference standards [25], and that both Xpert assay and DST can provide information on polyresistance in pre-XDR-TB [26] despite varying sensitivities [27,28]. The current practice in diagnosing drug resistant tuberculosis is through the WHO-approved probe-based assays like Xpert® MTB/RIF (Cepheid, USA) for RIF [16] and either genotype MTBDRplus for RIF and INH or genotype MTBDRsl (Hain Lifesciences, Germany) for aminoglycosides/capreomycin and fluoroquinolones that must be confirmed with culture-based DST [29]. Unlike WGS, these assays not only have limited DST range to identify hot-spot resistant determining regions but they also cannot inform transmission dynamics [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This study involved 57 and 30 participants who harboured M. tuberculosis that were resistant and susceptible to anti-TB drugs respectively, presenting at KIDH during the study period in 2014. Participants with resistant isolates were recruited if they had laboratory results by either GeneXpert MTB/RIF or phenotypic culture and DST [16]. The drug resistance was either mono/ polyresistance-resistant or MDR-TB.…”
Section: Study Design Population and Recruitment Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…From August 2018 to December 2019, longitudinal cohort study was conducted among patients with RR/MDR-and DS-TB confirmed using Xpert® MTB /Rif [9] . The study was approved by the National Institute for Medical Research (NIMR) in Tanzania (NIMR/HQ/R.8a/Vol.…”
Section: Patients Ethics and Designmentioning
confidence: 99%
“…Patients were recruited at KIDH, national centre of excellence for clinical management of drug resistant (DR)-TB located in the Siha district of Kilimanjaro region in Tanzania [9] . TB-MBLA testing was performed at the National Institute for Medical Research, Mbeya Medical Research Centre branch, given that laboratory's prior experience with the assay.…”
Section: Study Settingmentioning
confidence: 99%